Analisa Risiko Pendistribusian Kelapa Sawit Pada CV Afri Group Menggunakan Metode FMEA dan FTA - Afif, Muhammad; Hartati, Misra; Umam, Muhammad Isnaini Hadiyul; Yola, Melfa; Suherman, Suherman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
CV Afri Group is one of the middlemen (agents) buying and selling palm oil in Kunto Darussalam, Rokan Hulu Regency, Riau. this company is engaged in distributing palm oil to PKS, the palm oil distribution process does not always run smoothly there are risks that often occur in distribution. The risks that arise cause the distribution is not optimal. Risk management is needed to identify and detect problems in the distribution process. The FMEA method is a method used to identify the distribution process. Based on the FMEA method, there are 6 potential failures and 33 risk sub-indicators from the distribution process, such as Farmer Relations with the highest RPN value of 266.2, and based on the RPN value, 4 critical risks are obtained which will be analyzed by FTA to find roots. of existing problems